2022
DOI: 10.1108/intr-10-2021-0787
|View full text |Cite
|
Sign up to set email alerts
|

Fostering consumer engagement with marketer-generated content: the role of content-generating devices and content features

Abstract: PurposeThis research explores the impacts of content-generating devices (mobile phones versus personal computers) and content features (social content and achievement content) on consumer engagement with marketer-generated content (MGC) on social media. It also examines these factors' interaction effects on consumer engagement.Design/methodology/approachThe study analyzed MGC that 210 companies had posted to Sina Weibo over three years, testing the study’s proposed model with negative binomial regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…, 2022). Previous studies have shown that social interaction-oriented content can be measured by calculating social words' frequency in communication content (Tausczik and Pennebaker, 2010; Yang et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2022). Previous studies have shown that social interaction-oriented content can be measured by calculating social words' frequency in communication content (Tausczik and Pennebaker, 2010; Yang et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Words are the most basic unit through which ideas are expressed and specific words' frequency in information can reflect a communicator's communication strategy (Pezzuti et al, 2021). People can use social features in their language to express ideas about social (Yang et al, 2022). Previous studies have shown that social interaction-oriented content can be measured by calculating social words' frequency in communication content (Tausczik and Pennebaker, 2010;Yang et al, 2022).…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…61 FGC positively influences consumer engagement. 62 However, transactional content has a negative impact on consumer-contributed engagement, whereas entertainment content has a positive impact. 63 The above studies focus on the impact of firm-generated content in the text (product reviews, news reviews, social post comments, etc.)…”
Section: Hypotheses Of Fgv’s Influence Effect On Ugvmentioning
confidence: 99%